Nitrous Oxide Persistently Alleviates Pain Hypersensitivity in Neuropathic Rats: A Dose-Dependent Effect - Meric Ben Boujema; Emilie Laboureyras; Jan Pype; Baptiste Bessière; Guy Simonnet (Pain Research and Management)
BACKGROUND: Despite numerous pharmacological approaches, there are no common analgesic drugs that produce meaningful relief for the majority of patients with neuropathic pain. Although nitrous oxide (N2O) is a weak analgesic that acts via opioid-dependent mechanisms, it is also an antagonist of the N-methyl-D-aspartate receptor (NMDAR). The NMDAR plays a critical role in the development of pain sensitization induced by nerve injury.